Pengaruh Gender, Dukungan Atasan, Dan Proteksi Terhadap Keputusan Pengungkapan Kecurangan Pada Pemerintah Daerah Di Sumatera Barat - Lara Fatma Sarni; Herlina Helmy; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine empirically the influence of gender, superiors support, and protection of fraud disclosure decision local government in West Sumatra. This research is quantitative research. The population in this study were students of Master of Management at Universitas Negeri Padang and Master of Accounting at Universitas Andalas. The sample in this research was taken by using purposive sampling, namely 81 samples. The data collection method used is a survey method in the form of a questionnaire given personally. Data processing is performed using SPSS. The results of this research indicate that Gender does not significantly influence the decision to disclose fraud to local governments in West Sumatra. The results of hypothesis testing with two way ANOVA test (two way ANOVA), showed that the supervisor support variable gets a significant value of 0,000, it can be concluded that superiors support has a significant effect on fraud disclosure decisions in local governments in West Sumatra and the protection variable also gets significant value of 0,000, so it can be concluded that protection has a significant effect on fraud disclosure decisions in local governments in West Sumatra.